Highly differentiated "Topaz" rhyolite in the high plateau province of southern Peru - Noble, Donald C. (2002)
High-silica rhyolite is present in various parts of southern Perú. Rhyolite from two localites, the Cailloma caldera and the newly recognized Río Chalhuanca dome field, both in Arequipa Department, belong to the group of "topaz" rhyolites well known in the eastern and central parts ofthe Great Basin and New Mexico, Western U.S., and in many localities in Mexico ( e.g., Christian sen et al., Geol. S oc. Am. Spec. Paper 205). The Peruvian occurrences may be the first topaz rhyolites recognized in South America.